PENERAPAN PENGAJARAN REMEDIAL TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA POKOK BAHASAN IKATAN ION DAN IKATAN KOVALEN - Bukhari Bukhari (Jurnal Dedikasi Pendidikan, 2017)
This study aimed to analyze whether the application of remedial teaching can be used to improve student learning outcomes on the subject of ionic and covalent bonds. The population in this study were all students of class XI SMAN Peukan Bada consisting of 2 classes with the use of first class as a sample, totaling 30 students. In this study, the data collection instrument in the form of multiple-choice tests that have been tested for validity and reliability and awarded to students after the study material and the ionic bonding and covalent bonding after remedial teaching (remedial test). The results of data analysis showed that the level of completeness of student learning outcomes in individuals with absorption of 70% is 30% while the level of data completeness outcomes after remedial teaching 61% that of the percentage is concluded that an increase in student learning outcomes from 30% to 61% , This result indicates that results for students after teaching remedial increased by 31%. Hypothesis testing is used to test the two parties namely the t-test with the following data thitung = 4.09 and ttubel = 1.699 at a significance level of 0.05 and db = 29. Thus concluded that "the implementation of remedial teaching can be used to improve student learning outcomes in the subject of ionic and covalent bonding in class XI SMAN Peukan Bada